2011
DOI: 10.1063/1.3634052
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in hafnium oxide thin films

Abstract: We report that crystalline phases with ferroelectric behavior can be formed in thin films of SiO2 doped hafnium oxide. Films with a thickness of 10 nm and with less than 4 mol%. of SiO2 crystallize in a monoclinic/tetragonal phase mixture. We observed that the formation of the monoclinic phase is inhibited if crystallization occurs under mechanical encapsulation and an orthorhombic phase is obtained. This phase shows a distinct piezoelectric response, while polarization measurements exhibit a remanent polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
1,543
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,125 publications
(1,581 citation statements)
references
References 20 publications
26
1,543
4
8
Order By: Relevance
“…This analogy to ferroelectric Si:HfO 2 supports the hypothesis that the structural origin of spontaneous polarization in doped HfO 2 is linked to the stabilization of this particular phase and does not originate from the dopant itself. 5 The anti-ferroelectric like behavior observed for the fully stabilized Si:HfO 2 , however, was not observed in the Y:HfO 2 system within our experimental conditions. Tomida et al 16 clearly distinguished the tetragonal Si:HfO 2 from the cubic Y:HfO 2 system.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…This analogy to ferroelectric Si:HfO 2 supports the hypothesis that the structural origin of spontaneous polarization in doped HfO 2 is linked to the stabilization of this particular phase and does not originate from the dopant itself. 5 The anti-ferroelectric like behavior observed for the fully stabilized Si:HfO 2 , however, was not observed in the Y:HfO 2 system within our experimental conditions. Tomida et al 16 clearly distinguished the tetragonal Si:HfO 2 from the cubic Y:HfO 2 system.…”
Section: Resultsmentioning
confidence: 46%
“…reported for TiN=HfO 2 gate stacks 28 ) was identified to be the origin of the orthorhombic, ferroelectric, phase in SiO 2 -doped HfO 2 . 5 The increased P r observed in PMA samples at low YO 1.5 content suggests a larger ferroelectric phase fraction due to the suppressed monoclinic phase. However, even though PDA samples exhibit lower P r , they still show the presence of ferroelectricity, suggesting that the presence of a top electrode ("cap") is preferred, but not mandatory, for the formation of the ferroelectric phase in Y:HfO 2 thin films.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[10] Properties such as induced ferromagnetism and superconductivity have been observed due to broken symmetries at the interface [11] between a LaAlO3 substrate and a SrTiO3 film. Recently, strain-induced ferroelectric behavior has been observed in ca 10nm thick films of HfO2 [12] and Zr0.5Hf0.5O2 [13] on silicon. The appearance of ferroelectricity in oxide thin films with such simple compositions, when compared with conventional oxide ferroelectrics such as PbZrxTi1-xO3 is particularly interesting, as it offers the possibility for much easier integration of materials with useful active properties such as piezoelectricity, pyroelectricity, switchable polarization etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hafnium dioxide (HfO 2 ) based insulators have emerged as the primary contenders to replace traditional SiO 2 in a variety of nano-electronic devices ranging from deep-scaled transistors to DRAM 1,2 and non-volatile memory cells. 3,4 Furthermore, thanks to the ferroelectricity property of both doped 5,6 and pure 7 HfO 2 , novel applications including memories 8 and high sub-threshold slope transistors 9 are envisioned. However, the reliability of the dielectric associated with electron trapping appears to be the "show stopper": It has already been shown that the positive bias-temperature instability (PBTI) limits the gate oxide scaling in metal-HfO 2 -Si transistors [10][11][12][13] while in flash cells, electron trapping in the intergate HfO 2 insulator degrades the program/erase window, retention, and endurance.…”
mentioning
confidence: 99%